Technology and education: Challenges and opportunities - Cloete, Anita Louisa (HTS teologiese studies, 2017)
This article seeks to contribute to the continuous reflection on the integration of technology into education. In order to accomplish this aim, the use of technology in the form of blended learning and online education will be utilised to illustrate how technology plays a central role in education today. It is argued that technology should not merely be viewed as a tool, but rather as a medium that shapes culture. Therefore, the integration of technology into education should be accompanied by continuous reflection on the identifiable characteristics of technology as medium that is not value-neutral or a disembedded force. To the contrary, technology is socially embedded and could be directly linked to other social developments and processes. The article therefore wishes to highlight the social embeddedness of technology by stressing how it is intertwined with other social developments like economy. In order to utilise technology more effectively and in a responsible manner in education, the nature thereof as medium should be reflected on. In light of the discussion on the technology as a socially embedded medium, the possible challenges and opportunities that it poses as medium to education, are identified and discussed. Specific reference is made on how theological education could benefit from educational technologies.